2015
DOI: 10.1155/2015/617907
|View full text |Cite
|
Sign up to set email alerts
|

Race, Socioeconomic Status, and Age: Exploring Intersections in Preterm Birth Disparities among Teen Mothers

Abstract: Few studies have examined disparities in adverse birth outcomes and compared contributing socioeconomic factors specifically between African-American and White teen mothers. This study examined intersections between neighborhood socioeconomic status (as defined by census-tract median household income), maternal age, and racial disparities in preterm birth (PTB) outcomes between African-American and White teen mothers in North Carolina. Using a linked dataset with state birth record data and socioeconomic infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This association was also reported by Passing in Brazil, where the risk of preterm birth due to ANC visits <4 times was found to increase by 1.52 fold [11]. In Washington, it was found that the risk of preterm birth due to ANC visits <4 times increased by 5.7 times [21]. This difference in risk may be due to the fact that most of the women in our study were from rural areas where there is scarcity of health care services as compared to women in the previous studies [11,21].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This association was also reported by Passing in Brazil, where the risk of preterm birth due to ANC visits <4 times was found to increase by 1.52 fold [11]. In Washington, it was found that the risk of preterm birth due to ANC visits <4 times increased by 5.7 times [21]. This difference in risk may be due to the fact that most of the women in our study were from rural areas where there is scarcity of health care services as compared to women in the previous studies [11,21].…”
Section: Discussionsupporting
confidence: 76%
“…In Washington, it was found that the risk of preterm birth due to ANC visits <4 times increased by 5.7 times [21]. This difference in risk may be due to the fact that most of the women in our study were from rural areas where there is scarcity of health care services as compared to women in the previous studies [11,21]. The study in Brazil was a multicentre cross-sectional study and hence included a larger sample size as compared to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that women from richer households were more likely to use modern contraceptives compared to the poorest households. Household wealth generally is a predictive factor of many health outcomes, including the use of modern contraceptives as found by other studies [24,[32][33][34]. Household wealth may have provided Sierra Leone women with an opportunity for exposure to health information as well as giving them the purchasing power to afford a modern form of contraceptives.…”
Section: Plos Onementioning
confidence: 85%
“…Over 16% of black infants are born preterm compared to less than 11% of white infants(2). Differences in socioeconomic status(3), genetics(4), and personal health behaviors (such as smoking(5) and teenage pregnancy(6)) fail to completely explain racial disparities in preterm birth. Within racial/ethnic groups, poverty is a risk factor for preterm birth(7).…”
Section: Introductionmentioning
confidence: 99%